Pengembangan Multimedia Pembelajaran pengenalan Huruf Abjad untuk Anak Usia Dini (Paud) di TK Putri Pariama - Arief Fathur Rahman; Frihartini Ayu Salsabilah; Putri Wulandari (CV. ITTC INDONESIA, 2023)
The problem that often occurs in early childhood, one of which is in early childhood at Putri Pariama Kindergarten is that they find it difficult to capture knowledge orally because of children's learning patterns who like to play so that it can affect children's concentration in capturing learning knowledge both orally and in writing . This causes the limited basic knowledge of a child to understand the basic recognition of letters of the alphabet. The purpose of this research is to develop and produce a multimedia learning media in helping young children to recognize the letters of the alphabet. The method used in this study is to use data collection techniques through interviews and observations at TK Putri Pariama and this study uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The results of this study are that multimedia learning media for recognizing letters of the alphabet in early childhood (PAUD) in Putri Pariama Kindergarten is feasible to use and apply in order to increase children's learning interest in understanding alphabet recognition.